Educational interweavings: the continuity of living and an education of attention (Research, Society and Development, 2021)
In the present study, we produced a thread-writed, which allows us to mobilize the potentiality of thought of the anthropologist Tim Ingold, referring to the education of attention. We constitute a mesh of thought-writing that binds education as continuity of life, a movement dependent on a relational and attentional composition of communion and variation of knowledge and experiences between peers. Therefore, it is necessary to reactivate us an open experimentation, linked to compositions that demand the presence of a body disposed to learn to be affected, thoughtful in its relational dimensions, forward of the different existences that arrange the educational universe. In this sense, we instituted invitations: to move problematizations to producing spaces, practices, times, discourses, strategies, minor gestures, in Education.